Navigating the Transition: A Qualitative Inquiry into Hybrid Administrative Systems in a Regional Indonesian Junior High School - Sisi Suksesiawati; Sudarwan Danim; Asti Putri Kartiwi (Yayasan Sembilan Pemuda Indonesia, 2026)
While extensive scholarship addresses either fully manual or comprehensively digitalized school administration, transitional phases where both systems coexist remain critically underexplored. This qualitative single-case study examines how State Junior High School 03 of Central Bengkulu navigates digital transformation, revealing operational dynamics, efficiency implications, and strategic challenges inherent in hybrid administrative systems. Through interviews, document analysis, and observation with six administrative personnel, the investigation uncovers that digitalization remains confined to student affairs (Dapodik platform) and financial management (ARKAS system), whereas personnel administration, infrastructure management, and correspondence persist manually. This bifurcation creates duplication of effort, simultaneously enabling regulatory compliance while undermining operational efficiency. Four interconnected barriers emerged: intermittent internet connectivity, heterogeneous digital competencies, constrained budgets, and psychological resistance rooted in competence anxieties. These findings challenge linear stage models of technology adoption by demonstrating that hybrid systems in resource-constrained contexts function as semi-permanent organizational equilibria rather than temporary transitions. Theoretically, the study extends digital transformation scholarship by establishing hybridity as a distinct organizational form warranting its own analytical frameworks, not merely a developmental stage. Practically, findings inform context-sensitive implementation strategies for regional schools, emphasizing sequential roadmaps prioritizing high-impact domains, sustained competency development, and change management acknowledging staff apprehensions. This research contributes a reconceptualization of hybrid administration as potentially enduring rather than transitional, necessitating strategic management beyond linear digitalization assumptions.